Segmental dynamics of soccer instep kicking - Nunome, H.; Asai, T.; Ikegami, Y. (ISB Congress, 2005)
The purpose of this study was to reveal the detailed time-series actions of the resultant joint moment and motiondependent interactive moment during soccer instep kicking.